Optimizing material selection for brushed DC motor components using the VIKOR method: A comprehensive performance evaluation - Muhammad Nor Azril, Zulkafli; Mohd Azri Hizami, Rasid; Daing Mohamad Nafiz, Daing Idris (Springer Nature, 2025)
Excessive and unpredictable temperature rise in electrical machines can not only damage the motor over time but also induce errors in control systems within complex machinery. Conventionally, temperature reduction in electrical machines has been approached through geometric optimization of individual components. This study introduces an alternative strategy by selecting optimized material combinations for brushed DC motor components using the VIKOR multi-criteria decision-making (MCDM) method, focusing on thermal, electromagnetic, cost, and mass considerations. The proposed combinations were evaluated using a validated lumped parameter thermal network (LPTN) model, with further verification through finite element (FE) magnetic torque analysis and cost assessments. Results showed that the optimal material combination, consisting of a ferrite magnet, Al 356-T6 casing, chrome steel bearing, metal graphite brush, and nylon insulation, reduced winding temperature by 20 ℃ in a 5A copper losses test. This combination also preserved torque output within the core saturation limit and achieved a cost-effective, low-mass design. These findings validate VIKOR’s capability to holistically optimize material selection, offering a balanced approach that enhances thermal performance without compromising the motor’s functional and economic integrity.